EV Charging Using DC Storage and Sustainable Energy (International Journal of Innovative Research in Computer Science & Technology, 2022)
As countries and automakers focus on  initiatives such as "keeping green," climate action, and so  on, the present worldwide inclination favoring electric  vehicles is growing. An inherent aspect of this is the design  of electric cars. Electric automobiles run on energy  provided by a power source, which is often batteries. These  batteries must be recharged. As a result, a charging station  must be available. Various generators are converted into  Electrical output for the car at public charging or terminals. As countries and automakers focus on issues such as  "being green," climate action, and so on, the present  worldwide inclination favouring electric vehicles is  growing. The fact that there is a major source of this is a  major element of this system of electric cars. Electric  automobiles run on energy provided by a power source,  which is often batteries. These batteries must be recharged.  For this As a result, a rechargeable battery is required.  Various generators are converted into Useful electricity for  the car at public charging or terminals.
Keywords: DC Storage; Electrical automobiles; Batteries